2003
DOI: 10.1046/j.1460-9592.2003.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of J–ST‐Segment Elevation by the Glucose and Insulin Test in Brugada Syndrome

Abstract: The effects of glucose and insulin on J-ST-segment elevation were evaluated in seven men (mean age 45 +/- 10 years) with Brugada syndrome. Six patients had been reanimated from VF and one patient had experienced syncope. The effects of intavenous (1) pilsicainide 50 mg, (2) glucose 50 g, and (3) glucose 50 g plus regular insulin 10 IU on the precordial ECG leads were examined. Pilsicainide significantly enhanced J-ST elevation in all patients and induced VF in 1 patient. A significant accentuation of the abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 15 publications
3
40
2
Order By: Relevance
“…They found the accentuation of ST-segment in high-risk Brugada syndrome patients. However, the changes of blood glucose (BG) in this study were not directly related to the ECG changes [17]. Another study by Nishizaki assessed oral glucose tolerance test (OGTT) in Brugada syndrome patients and control healthy subjects.…”
Section: Brugada Syndrome and Carbohydrate Metabolismmentioning
confidence: 65%
“…They found the accentuation of ST-segment in high-risk Brugada syndrome patients. However, the changes of blood glucose (BG) in this study were not directly related to the ECG changes [17]. Another study by Nishizaki assessed oral glucose tolerance test (OGTT) in Brugada syndrome patients and control healthy subjects.…”
Section: Brugada Syndrome and Carbohydrate Metabolismmentioning
confidence: 65%
“…ST segment elevation in BS is often dynamic. The Brugada ECG may often be concealed, but can be unmasked or modulated by sodium channel blockers, a febrile state, vagotonic agents, α-adrenergic agonists, β-adrenergic blockers, tricyclic or tetracyclic antidepressants, firstgeneration antihistaminics (dimenhydrinate), a combination of glucose and insulin, hyperkalemia, hypokalemia, hypercalcemia, and by alcohol and cocaine toxicity [37][38][39][40][41][42][43][44][45][46][47]. These agents may also induce acquired forms of BS.…”
Section: Antidepressant and Antipsychotic Drug-induced Brugada Syndromementioning
confidence: 99%
“…A recent study by Nogami et al showed that glucose and insulin could unmask the Brugada ECG marker or accentuate the J-junction elevation of the ST-segment. 74 They observed a slight decrease in the serum potassium levels of their study patients, but it did not reach statistical significance. Nevertheless, these findings bode well for a heavy carbohydrate meal being a precipitating factor for sudden death in SUDS patients.…”
Section: Sleep and Heavy Mealsmentioning
confidence: 82%